PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) PADA MATERI TEKS BERITA KELAS XI - Tri Wahyu Setyaningrum; Asrofah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
ABSTRACT This research is motivated by the fact that students when learning collaboratively do not all have the same learning abilities and active involvement. Therefore, researchers have a solution to overcome this problem. The Teams Games Tournament (TGT) type of cooperative learning model is one of the useful learning models for enhancing students' activities in class. The research methods used are qualitative and descriptive. There are five steps in implementing the TGT learning model, namely 1) conveying information, 2) team formation, 3) games, 4) tournaments, and 5) group awards. By implementing the Teams Games Tournament (TGT) type cooperative learning model, the goals of the learning process can be achieved if Students participate actively in lessons and in group assignments. Apart from that, the TGT (Teams Games Tournament) model integrates students with 21st Century skills which are really needed when students move in the world of society, namely, in discussion and presentation activities (Communication), collaborating in groups (Collaboration), question and answer, responding, answering questions (Critical thinking), and presenting the results of discussions and assessments in an interesting way (Creativity). Keywords: Learning model, TGT ABSTRAK Penelitian ini dilatarbelakangi oleh peserta didik ketika pembelajaran kolaborasi, tidak semua memiliki daya belajar dan keterlibatan aktif yang sama. Oleh kerena itu, peneliti mempunyai solusi untuk mengatasi pemecahan masalah tersebut. Tipe Teams Games Tournament (TGT) dari model pembelajaran kooperatif ialah satu diantara model pembelajaran bermanfaat untuk mempertinggi kegiatan aktivitas dari peserta didik di kelas. Penggunaan metode penelitian yakni kualitatif dan deskriptif. Terdapat lima langkah penerapan model pembelajaran TGT yaitu 1) menyampaikan infromasi, 2) pembentukan tim, 3) permaian, 4) turnamen, dan 5) penghargaan kelompok Dengan menerapkan model pembelajaran kooperatif tipe Teams Games Tournament (TGT), tujuan proses belajar dapat dicapai jika peserta didik berpartisipasi aktif dalam pelajaran dan dalam penugasan kelompok. Selain itu, model TGT (Teams Games Tournament) mengintegrasikan peserta didik dengan kemampuan Abad-21 yang sangat dibutuhkan ketika peserta didik bergerak dalam dunia masyarakat yaitu, pada kegiatan berdiskusi dan presentasi (Communication), melakukan Kerjasama dalam kelompok (Collaboration), tanya jawab, menanggapi, menjawab soal(Critical thinking), dan memaparkan hasil diskusi dan penilaian dengan menarik (Creativity). Kata kunci: Model pembelajaran, TGT